ANALISIS BIBLIOMETRIK TENTANG PENGGUNAAN APLIKASI CANVA SEBAGAI SARANA PEMBELAJARAN MATEMATIKA PADA SISWA SEKOLAH DASAR - Sudrajat (Elementary School and Education Journal, 2026)
The Canva application as an alternative interactive mathematics learning tool. The numerous studies on the use of the Canva application in mathematics learning require analysis of the research results. Therefore, the purpose of this study is to identify the results of previous studies on trends and research focuses regarding the use of the Canva application as a mathematics learning tool for elementary school students and visualize them. This research sample was obtained from the Google Scholar database of 392 published articles that had gone through the data collection process, namely identification, screening, eligibility, and inclusion. The results show that the publication trend from 2021-2025 has increased significantly. The citation trend in 2023 is a very influential citation in this study compared to other studies. This citation trend can also be seen from the number of citations of 1,580 citations, h-index 19 and g-index 34. The focus of this research is divided into seven, namely learning; applications; teachers and classes; elementary schools; mathematics learning media, and students; mathematics; Canva and mathematics learning; and grade IV elementary school and development. New themes and novelties regarding this research have been discussed in the discussion and can be used as an alternative for further research.